A bright side of financial constraints in cash management - Luo, Mi (Meg) (Journal of Corporate Finance, 2011)
This paper tests whether financial constraints play a disciplinary role in cash dissipation in the presence of agency problems. We hypothesize that when firms have difficulty raising external funds, empire-building managers of cash-rich firms will be less likely to spend cash on negative NPV projects as compared to unconstrained managers. Empirically, we examine firm performance after cash dissipation and associate it with the degree of financial constraints. We find that cash spending by managers in financially constrained firms is associated with higher future profitability and stock returns compared to cash spending by managers in unconstrained firms. Further tests reveal that the positive effect of financial constraints on firm performance is not driven by differences in corporate governance. Financial constraints actually substitute for good governance in disciplining managers. We find that corporate governance improves the efficiency of cash dissipation in unconstrained firms, but not in constrained firms. Likewise, financial constraints' disciplinary effect is found to be concentrated in firms that are poorly governed.